Atropine is more efficient than ZM241385 to reduce a drastic level of fade caused by cisatracurium at 50 Hz - Pimentel, Arethusa Lobo; Prado, Gabriela de Castro; Alves-Do-Prado, Wilson; Ambiel, Célia Regina (Acta Scientiarum. Health Sciences, 2016)
The effects of atropine (non selective muscarinic antagonist) and ZM241385 (A2A receptors antagonist) in the cisatracurium-induced drastic (100%) level of fade at 50 Hz (10 s) (100% Fade) were compared in the phrenic nerve-diaphragm muscle preparations of rats indirectly stimulated at a physiological tetanic frequency (50 Hz). The lowest dose and the instant cisatracurium caused 100% Fade were investigated. Cisatracurium induced 100% Fade 15 min after being administered. Atropine reduced the cisatracurium-induced 100% Fade, but the administration of ZM241385 separately, or combined with atropine, did not cause any effect in the cisatracurium-induced 100% Fade. Data indicate that the simultaneous blockage of M1 and M2 muscarinic receptors on motor nerve terminal by atropine is more efficient than the blockage of presynaptic A2A receptors for a safer recovery of patients from neuromuscular blockade caused by cisatracurium.